The Impact of Online Apps Hotels, Customer Wellbeing and Customer Citizenship Behavior: A Mediating Role of Customer Intimacy - Hasnin, Eman Abdel Hameed (Journal of Ecohumanism, 2025)
This study aims to assess how customer well-being influences customers’ citizenship behavior nowadays, tourism and hotel organizations care about their customers. By studying their behaviors and satisfaction levels, one of these trends is to determine the level of customers’ well-being and build intimate relationships with them. Although there is a wide range of research on customer well-being, the impact of customer well-being, customer intimacy, and customer citizenship behavior has not received enough empirical investigation. This study aims to fill this gap. In addition, we examine the mediating role of customer intimacy. Partial least squares structural equation modeling (Warp-PLS V.7) and SPSS 26.0 were used to analyze data collected from 333 hotel customers in Cairo. The results show that customer well-being has both direct and indirect effects on customers’ citizenship behavior, with customer intimacy acting as a partial mediator. The results of the study provide useful guidelines that can help hotel managers make more efforts to enhance customer relationships, achieve customer well-being, achieve customer citizenship, achieve customer intimacy, and benefit from its mediating role in the relationship.